Local Governance Lessons from Turkey’s System: Enhancing Local Governance in Afghanistan - (:unkn) unknown (My University, 2021)
Historically Turkey and Afghanistan have had strong centralist administrative systems that demonstrate relative institutional flaws at the local level. Afghanistan as a country that is emerging from decades of instabilities has adopted a new legal framework for its local administration under the 2004 Constitution. Likewise, Turkey’s local administrative system has applied various reforms under the 1982’s Constitution. Although both countries’ constitutions delegate a certain amount of authorities and responsibilities at the sub-national level, local administrations are subjected to strong administrative and financial tutelage of central governments in both countries. In Turkey, local elections matter relatively on the functionality of public institutions and local democracy, whereas in Afghanistan, major local authorities still representing central government, and people at the local level have no role in making public decisions. Since Turkey’s experience on modern state-building has had a significant influence on shaping the first constitution of Afghanistan, recent reformations, successful or failed, can be lessons for Afghanistan as a country that is in the process of state-building to empower its public institutions, bring peace and rehabilitate participatory governance. This paper aims to compare the evolution, structure, and function of the local government system in Turkey and Afghanistan to clarify the question of authority and autonomy level for local governance in both countries. The author in this research examines constitutional provisions, legislation, policies of both countries regarding the interrelationship of the central government and local unites to highlight the mechanism of people’s engagement with states and offers specific recommendations at the end of this paper.

Tarihsel olarak Türkiye ve Afganistan, yerel düzeyde göreceli kurumsal kusurlar gösteren güçlü merkeziyetçi idari sistemlere sahip olmuştur. Afganistan, onlarca yıllık istikrarsızlıktan doğan bir ülke olarak, 2004 Anayasası kapsamında yerel yönetimi için yeni bir yasal çerçeve benimsemiştir. Aynı şekilde Türkiye'de yerel yönetim sistemi de 1982 Anayasası kapsamında çeşitli reformlar hayata geçirilmiştir. Her iki ülkenin anayasaları da belirli bir miktarda yetki ve sorumlulukları ulus altı düzeye devretse de yerel yönetimler her iki ülkede de merkezi devletlerin güçlü idari ve mali vesayetine tabidir. Türkiye'de yerel seçimler kamu kurumlarının işlevselliği ve yerel demokrasi açısından nispeten önemlidir. Afganistan'da ise merkezi devleti temsilcisi konumundaki yerel yönetim kurumları ve vatandaşların anayasanın onlara tanıdığı haklar çerçevesinde kamusal kararların alınmasında hiçbir rolleri yoktur. Türkiye'nin modern devlet inşası konusundaki deneyimi, Afganistan'ın ilk anayasasının şekillenmesinde önemli bir etkiye sahip olduğundan, başarılı veya başarısız sonuçları olan son reformlar, kamu kurumlarını ve katılımcı yönetişimi güçlendirmek için devlet kurma sürecinde olan Afganistan için önemli tecrübeler sunuyor. Bu makale, her iki ülkede de yerel yönetişim için yetki ve özerklik düzeyi sorununu açıklığa kavuşturmak için Türkiye ve Afganistan'daki yerel yönetim sisteminin evrimini, yapısını ve işlevini karşılaştırmayı amaçlamaktadır. Bu araştırma, vatandaşların devletlerle etkileşim mekanizmasını vurgulamak için merkezi devletler ve yerel bileşenler arasındaki karşılıklı ilişkilere ilişkin anayasal hükümler, mevzuat ve politikaları incelemekte ve önerilerde bulunmaktadır.
Türkiye Sisteminden Yerel Yönetim Dersleri: Afganistan'da Yerel Yönetimin Geliştirilmesi